New taxa in the subtribe Oncidiinae (Orchidaceae) - Szlachetko, Dariusz L.; Górniak, Marcin (Biodiversity: Research and Conservation, 2006)
A new genus - Brassiopsis Szlach. & Górniak gen. nov. - of the subtribe Oncidiinae (Vandoideae, Orchidaceae) is described. New combinations on the species level in the genera Brassiopsis and Collare-stuartense Senghas & Bockemuhl are proposed.